COGNITIVE LINGUISTICS: EXPLORING THE INTERCONNECTION BETWEEN LANGUAGE, COGNITION, AND EXPERIENCE - Zaynieva Gulchaman Ilhomjon qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Cognitive linguistics constitutes an interdisciplinary framework that examines language as an integral component of human cognitive functioning rather than as an isolated, innate system. It emphasizes that linguistic meaning arises from conceptual structures shaped by bodily experience, cultural knowledge, and patterns of language  use.  This  article  offers  a  synthesized  account  of  Cognitive  linguistics  by outlining its theoretical origins, foundational assumptions, methodological orientation, and central domains of inquiry, including conceptualization, metaphor, embodiment, and usage-based grammar. Drawing on influential contributions by Langacker, Lakoff, Talmy, and subsequent scholars, the study demonstrates that meaning construction is dynamic,  experience-based,  and  cognitively  motivated.  The  findings  underline  the significance  of  Cognitive  linguistics  for  contemporary  linguistic  theory  and  its applications in applied linguistics and cognitive science.